INDIGOFERA PULCHRA: A POTENTIAL FODDER IN WEST AFRICAN SAVANNA - JAYEOLA, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The potential uses of indigofera pulchra Wild., a wild herbaceous legume of West African Savanna was investigated in four different savanna zones. It was observed that I. pulchra remains green throughout the critical period of the dry season when fodder is most limiting for livestock production. I. pulchra can also fix atmospheric nitrogen. There is consistent evidence that I. pulchra grows in association with Pennisetum pedicellatum Trin., Andropogon gayanus Kunth., Hyparrhenia involucrata Stapf and Clenium newtonii. N2-concentration encountered in I. pulchra is higher than ever recorded for any West African grass, though only at P<0.1) The suggestion is being made that I. pulchra may be selected for use in improved ranges.